Comparative analysis of coping capacity in participants of military actions with eyes injury and partial vision loss amidst psychological maladaptation or post-traumatic syndrome - Abdryakhymov, Rostislav (Journal of Education, Health and Sport, 2019)
The aim of this work was a comparative study of coping strategies in participants of military actions with eyes injury and partial loss of vision amidst clinical manifestations of psychological maladaptation or post-traumatic syndrome in order to determine further targets for medical and psychological rehabilitation measures. Under the condition of informed consent with adhering to the principles of bioethics and deontology during 2014–2018 years, 191 participants of military actions (PMA) were examined. The age of the surveyed was 20–53 years. For comparison, the study included 59 men with partial loss of vision (PVL) due to household injuries which made the comparison group (CG). All respondents were screened for a mental state using a clinical diagnostic scale CAPS (Clinical-administered PTSD Scale), a questionnaire for determining the level of neuroticism and psychopathisation, they were consulted by a psychiatrist and a psychodiagnostic study was carried out. The following study groups were formed. Major groups: (MG1) – 54 PMA with eyes injury and PVL due to participation in military actions with clinical manifestations of post-traumatic syndrome; (MG2) – 49 PMA with eyes injury and PLV due to participation in military actions with manifestations of psychological maladaptation. Comparison groups: group 1 (CG1) – 46 PMA with clinical manifestations of post-traumatic syndrome; group 2 (CG2) – 42 PMA with psychological maladaptation; group 3 (CG3) – 59 men with PLV due to household injuries. The study found the following. With the phenomena of psychological maladaptation in the emotional, cognitive and behavioral areas, unproductive and relatively productive coping strategies dominated. They were accompanied by changes in behavioral and communicative levels, decrease in adaptive capacity of the personality and predisposition to asthenic manifestations. Eyes injury amidst psychological maladaptation is accompanied by the development of unproductive and relatively productive coping strategies on the cognitive, emotional and behavioral levels. This was accompanied by deterioration of the level of behavioral regulation and asthenic reactions. A significant advantage of unproductive emotional coping strategies with manifestations of post-traumatic disorder was found. Their use by the person led to the deterioration of behavioral and diffuse disorganization of cognitive coping strategies. According to the outputs of the personal questionnaire “Adaptability”, this was accompanied by a deterioration of cognitive potential. Eyes injury with partial loss of vision amidst the clinical manifestations of post-traumatic syndrome leads to a deterioration of productivity of the formed coping strategies. These disorders are also much more manifested than an injury amidst psychological maladaptation. Maladaptation disorders have no differences and dependence on the phenomena of psychological maladaptation or clinical manifestations of post-traumatic syndrome. The obtained results will be taken into account when creating specialized highly-target approaches to medical and psychological rehabilitation for this contingent.